2005
DOI: 10.4049/jimmunol.175.3.1498
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Infection Dramatically Augments Lipopolysaccharide-Induced TNF Production and Sensitizes to Lethal Shock

Abstract: We observed a remarkable synergism of adenoviruses and LPS in triggering the production of TNF in intact animals. We found that in mice pre-exposed to adenoviruses, LPS injections generated extremely high levels of TNF with altered kinetics. The elevated TNF synthesis stemmed mostly from posttranscriptional up-regulation of TNF production, although transcription of the TNF gene was also induced. Adenoviruses and LPS exhibited a significant but less dramatic synergism in the induction of IL-6, IFN-γ, and NO. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 50 publications
3
40
1
Order By: Relevance
“…As IFN␥ is not produced in abundance by phagocytes, and is expressed in mouse lymphocytes (26), the mechanism appears to involve cross talk between the innate and the acquired arms of the immune system. IFN␥ has been shown not only to increase TLR expression but also to prime cells to LPS responses in a number of experimental infections (27)(28)(29)(30) and has also been pointed as crucial to prime macrophages to release high amounts of TNF upon LPS administration and contribute to LPS induced septic shock (31). We (12) and others (14) have shown that TLR9 accounts for a considerable amount of IFN␥ produced during malaria.…”
Section: Discussionmentioning
confidence: 99%
“…As IFN␥ is not produced in abundance by phagocytes, and is expressed in mouse lymphocytes (26), the mechanism appears to involve cross talk between the innate and the acquired arms of the immune system. IFN␥ has been shown not only to increase TLR expression but also to prime cells to LPS responses in a number of experimental infections (27)(28)(29)(30) and has also been pointed as crucial to prime macrophages to release high amounts of TNF upon LPS administration and contribute to LPS induced septic shock (31). We (12) and others (14) have shown that TLR9 accounts for a considerable amount of IFN␥ produced during malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Suboptimal concentration of IFN-γ does not trigger immune cells, instead, it primes for subsequent response upon stimulation, but, in excess, can eventually cause deleterious consequences. This IFN-γ priming effect has been increasingly implicated in the immune response to several infectious diseases, including viral, bacterial, and parasitic diseases [12][13][14]. For brucellosis, the crucial role of IFN-γ was recognized, as it was shown that IFN-γ knockout mice died due to B. abortus infection and IFN-γ producing CD4+ T-cells from infected donors were able to protect the recipient mice against challenge with B. abortus [15].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Ad-induced early-type I IFN production mediates a very strong LPS hypersensitivity characterized by the dramatic overproduction of TNF (50-100-fold) and IL-6 (5-10-fold) [88]. Furthermore, there is a strong overproduction of nitric oxide (NO), mostly in spleen [88]. Interestingly, LPS injection of uninfected control animals elicits NO production mainly in liver.…”
Section: Ad-induced Lps Hypersensitivitymentioning
confidence: 99%
“…In these cases, early production of IFN-αβ 2-3 days after infection mediates a relatively weak (2-4-fold) hypersensitivity (or even downregulation of TNF production ) [92], while later (after 7 days) IFN-production mediates a strong hypersensitivity to LPS, characterized by the overproduction of TNF [89][90][91][92][93]. In contrast, Ad-induced early-type I IFN production mediates a very strong LPS hypersensitivity characterized by the dramatic overproduction of TNF (50-100-fold) and IL-6 (5-10-fold) [88]. Furthermore, there is a strong overproduction of nitric oxide (NO), mostly in spleen [88].…”
Section: Ad-induced Lps Hypersensitivitymentioning
confidence: 99%
See 1 more Smart Citation